65.1: A Vertically‐Aligned LCOS with Submillisecond Response Time. Issue 1 (1st July 2013) - Chen, Yuan; Peng, Fenglin; Wu, Shin‐Tson; Mo, Lingchao; An, Zhongwei
Abstract: We demonstrated a TFT‐grade fluorinated, UV‐stable, high birefringence and low viscosity negative Δε LC mixture and characterized its physical properties. With this mixture in a thin‐cell‐gap LCOS, we can achieve submillisecond response time at an elevated temperature, which enables color sequential projection displays without noticeable color breakup.